2021
DOI: 10.12669/pjms.37.3.3923
|View full text |Cite
|
Sign up to set email alerts
|

Aftermath of traumatic tympanic membrane perforation: Our findings at a tertiary care hospital in Pakistan

Abstract: Objectives: To determine the outcome of traumatic tympanic membrane perforation in a teaching hospital at Peshawar, Pakistan. Methods: This prospective observational study was performed in the Department of ENT and Head and Neck Surgery, MTI/LRH, Peshawar, Pakistan from January 2016 to December 2019 after approved from Institutional Research and Ethical Board. All consented patients fulfilling inclusion criteria were enrolled. Sample size was calculated 114 using online sample size calculator (OpenEpi). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 12 publications
2
1
0
Order By: Relevance
“…This study, 124 cases were included with a male preponderance (57.3%) with a sex ratio of 1.34. This is consistent with the analysis by Wahid FI et al Performed in Pakistan, which included 114 male-dominated patients (71%) with a sex ratio of 2.5 [2]. The mean age of the patients in our study was 28.6 years, close to the study done in Germany in 2015 by Kraus et al on traumatic tympanic perforations, which had an average age of 28.7 years [3].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This study, 124 cases were included with a male preponderance (57.3%) with a sex ratio of 1.34. This is consistent with the analysis by Wahid FI et al Performed in Pakistan, which included 114 male-dominated patients (71%) with a sex ratio of 2.5 [2]. The mean age of the patients in our study was 28.6 years, close to the study done in Germany in 2015 by Kraus et al on traumatic tympanic perforations, which had an average age of 28.7 years [3].…”
Section: Discussionsupporting
confidence: 92%
“…similar to those of one of the studies mentioned above by Wahid FI et al In Pakistan in 2021, 72.9% of post-blast tympanic perforations were caused by slapping [2]. These findings are also reinforced by a study done in Bangladesh in 2015 by Rabbani SG et al on traumatic tympanic perforations, which reported that 88.5% of cases were caused by slapping [6].…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation